EL MONSTRUO FEMENINO. LO SINIESTRO Y LA CONSTRUCCIÓN DE LO MATERNO EN FURTIVOS - Dra. Silvia GUILLAMÓN CARRASCO (Fonseca, Journal of Communication, 2023)
The maternal figure embodies one of the most recurrent metaphors in Spanish cinema of late-Francoism and transition, a metaphor that has been read as a device of social criticism towards the dictatorship. Largely due to the symbolic connotations that the Franco regime had projected on motherhood, it has been connected with the dictatorial past, functioning on the screen as a monstrous and uncanny personification of the Francoist repressive apparatus. Thus the maternal has become a privileged space for the deployment of film narratives that explore how power relations within the family can be portrayed as a symbol of the relationship between the subject and the State